Visible-light-driven hydrogen evolution from waste toner powder activated by Ni species. Issue 3 (24th January 2022) - Zhang, Wenyan; Guan, Hangmin; Hu, Yingfei; Wang, Wei; Hao, Linyun; Yang, Xiaoli; Tian, Wenjie
Abstract : This work reports visible-light-driven hydrogen evolution with waste toner activated with a Ni species as the photocatalyst, which is a promising approach for making good use of waste toner in clean energy production. Abstract : With the dramatic increase in the application of modern office equipment, such as laser printers and photocopiers, large amounts of waste toner powder are used and discarded, ending up in landfills around the world. As waste toner powder contains hazardous compounds that can seriously endanger both the environment and human health, it is urgent to deal with waste toner powder and convert it into high value-added products. In this work, we report, for the first time, visible-light-driven hydrogen production with waste toner activated by cheap Ni species (waste toner@Ni-species) as the photocatalyst. The Ni species adhered to the waste toner through in situ photoreduction, without sophisticated equipment. It is found that the Ni species were composed of metallic Ni and oxidized Ni, which worked in synergy to remarkably enhance the photocatalytic activity of the waste toner. Activated by the Ni species, the hydrogen evolution rate of the waste toner was accelerated by up to 62 times, and the apparent quantum efficiencies (AQEs) of the waste toner were boosted by up to 64 times. In addition, the waste toner@Ni-species exhibited a higher charge separation efficiency, faster interfacial charge transfer rate and ∼200 mV lower barrier for proton reduction than those of the pristine waste toner. In addition to these merits, the waste toner@Ni-species could be separated conveniently from the aqueous system using magnetic attraction, as the saturation magnetization and residual magnetism of the waste toner were improved with the assembly of the Ni species. The approach shown here indicates a simple and promising way to deal with waste toner by converting it to a cost-effective photocatalyst for producing clean energy.